eDNAir: proof of concept that animal DNA can be collected from air sampling - Clare,Elizabeth L.; Economou,Chloe K.; Faulkes,Chris G.; Gilbert,James D.; Bennett,Frances; Drinkwater,Rosie; Littlefair,Joanne E. (PeerJ, 2021)
Environmental DNA (eDNA) is one of the fastest developing tools for species biomonitoring and ecological research. However, despite substantial interest from research, commercial and regulatory sectors, it has remained primarily a tool for aquatic systems with a small amount of work in substances such as soil, snow and rain. Here we demonstrate that eDNA can be collected from air and used to identify mammals. Our proof of concept successfully demonstrated that eDNA sampled from air contained mixed templates which reflect the species known to be present within a confined space and that this material can be accessed using existing sampling methods. We anticipate this demonstration will initiate a much larger research programme in terrestrial airDNA sampling and that this may rapidly advance biomonitoring approaches. Lastly, we outline these and potential related applications we expect to benefit from this development.
Keywords: airDNA; eDNA; Biomonitoring; Biodiversity; Terrestrial